ANALYSIS OF THE MOTIVES AND LEVEL OF SATISFACTION OF USERS OF VIDIO.COM AS STREAMING MEDIA IN INDONESIA - Muhammad Alfinka Dwiana Putra Pamuji; Daru Purnomo; Seto Herwandito (Bajang Institute, 2023)
This research is entitled